Dictyostelids Evolution, Genomics and Cell Biology - Romeralo, Maria; Baldauf, Sandra; Escalante, Ricardo (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Since their discovery in 1869, the dictyostelids have attracted the attention of scientists in a wide variety of fields. This interest has stemmed from their peculiar lifestyle and developmental properties, which were shaped by the evolutionary forces that generated multicellularity during eukaryotic evolution. More recently, the dictyostelids have gained attention due to the striking similarities found at the genomic, cellular and biochemical levels with human cells, which has propelled the species Dictyostelium discoideum to become a model system for biology and medicine in many laboratories. This book covers the latest advances in our knowledge of these extraordinary organisms with topics spanning from their evolutionary history, ecology and diversity to the recent discoveries regarding their cellular and molecular biology.